Application of The Rasch Model in The Development of Dimension of The Measurement of Tax Fairness Perception Measurement of Tax Fairness Perception - Larasati, Meita; Mukri, Cotoro (Universitas Muhammadiyah Surakarta, 2020)
This study aims to investigate the measurement instrument of the perception dimension of tax fairness using the Rasch model method. The dimensions of the perception of tax fairness are divided into seven dimensions, namely general fairness, exchange fairness, horizontal fairness, vertical fairness, retributive fairness, policy fairness, and administrative fairness. The sampling technique employed purposive sampling by classifying several criteria for respondents. The distribution of data used Google docs to as many as 122 individuals. The results of this study indicate that the Cronbach alpha value (KR-20) is 0.71. The question item with code PF2 which is included in the personal fairness dimension with a logit value of +0.91 is the most difficult item for respondents to answer. There are three question items that are considered misfit because the logit value of the item is greater than the sum of the mean and standard deviation (1.27). The three items are VF 1 (1.72), RF1 (1.48), and EF2 (1.29). The contributions of this study are: (1) to enrich the literature on tax fairness perceptions by using the Rasch model as a data analysis tool, and (2) empirically, to validate the measurement instrument in the perception of tax fairness dimensions which will be useful for further research.